Role of nidi of infection in various skin diseases - A. V. Patrushev; A. V. Sukharev; A. M. Ivanov; A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Reviewed scientific publications that define the location of foci of chronic infections in dermatology. Indicated by the currently existing problematic issues and their solutions.